2016
DOI: 10.1016/j.schres.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The relations of age and pubertal development with cortisol and daily stress in youth at clinical risk for psychosis

Abstract: BACKGROUND Prodromal syndromes often begin in adolescence – a period of neurodevelopmental changes and heightened stress sensitivity. Research has shown elevated stress and cortisol in individuals at clinical high risk (CHR) for psychosis. This cross-sectional study examined relations of age and pubertal status with cortisol and self-reported stress in healthy controls (HCs) and CHR adolescents. It was hypothesized that the relations of age and pubertal stage with cortisol and stress would be more pronounced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
1
13
0
2
Order By: Relevance
“…Similarly, CHR patients who later converted to psychosis reported a greater number of life events, and perceived these events as more stressful, compared to healthy controls and CHR subjects whose symptoms remitted (Trotman et al, 2014). Perceived stress levels in CHR patients are generally high (Moskow et al, 2016), and in some studies they even exceed ratings in FEP patients (Pruessner et al, 2011, Palmier-Claus et al, 2012.…”
Section: Stress Exposure Perceived Stress and Early Life Adversitymentioning
confidence: 97%
“…Similarly, CHR patients who later converted to psychosis reported a greater number of life events, and perceived these events as more stressful, compared to healthy controls and CHR subjects whose symptoms remitted (Trotman et al, 2014). Perceived stress levels in CHR patients are generally high (Moskow et al, 2016), and in some studies they even exceed ratings in FEP patients (Pruessner et al, 2011, Palmier-Claus et al, 2012.…”
Section: Stress Exposure Perceived Stress and Early Life Adversitymentioning
confidence: 97%
“…As dictated by our inclusion criteria, all studies included a healthy control group and at least one psychosis spectrum group. Four studies included both high-risk and established psychosis subgroups (48,51,53,55), eight included established psychosis groups only (46,49,52,54,65,(67)(68)(69), and six examined high-risk groups only (31,47,50,56,60,66). The most commonly-examined established psychosis subgroup was FEP (n=5), a further study examined recent-onset psychosis (49) which included FEP patients, two studies included patients with psychotic disorder where the stage of illness was not indicated (53,67), three studies included patients with schizophrenia (52,54,69), while a further study distinguished between patients with early and chronic schizophrenia (55).…”
Section: Group Status and Psychosis Spectrum Definitionsmentioning
confidence: 99%
“…Control groups varied in size, ranging from 25 (68) to 133 (46), the latter study also comprised the largest established psychosis group (n=169). With regards to high-risk group sizes, the smallest comprised of 21 UHR individuals (48) with the largest including 348 UHR youth from the NAPLS-2 study (66). Participants in the high-risk groups were the youngest on average (mean age = 23.7 years; range: 12.8 to 42.9 years), followed by healthy controls (mean age = 27.2 years; range 13.1 to 43.5 years), with the oldest being those with established psychosis (mean age = 31.1 years; range 20.6 to 43.8 years).…”
Section: Sample Sizes and Demographic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations